MANAGING STUDENT ANXIETY IN LEARNING MATHEMATICS - Astri Setyawati (Universitas Nahdlatul Ulama Lampung, 2018)
Learning mathematics is a form of government attention to the development of mathematics, which is one of the fields of science that has become a milestone for the progress of a country. This development effort does not just go away, there are obstacles that occur, especially those related to mathematics learning or the views of some students towards mathematics itself. Anxiety is one of the things that hit the learning system, especially mathematics learning. Students' anxiety in mathematics learning can be interpreted as an unpleasant emotional state of students, which is characterized by anxiety, discomfort, worry, unfounded fear that undesirable things will happen when students face maths lessons. The anxiety experienced by students in mathematics is often referred to as mathematics anxiety (Mathematics Anxiety). Mathematics anxiety cannot be seen as normal, because the inability of students to adapt to lessons causes students to have difficulty and phobia towards mathematics, which in turn causes student achievement in mathematics to be low. This paper willdescribe several things that can manage anxiety in learning mathematics.